2014
DOI: 10.1002/cmdc.201300525
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode and Structure–Activity Relationships around Direct Inhibitors of the Nrf2–Keap1 Complex

Abstract: An X-ray crystal structure of Kelch-like ECH-associated protein (Keap1) co-crystallised with (1S,2R)-2-[(1S)-1-[(1,3-dioxo-2,3-dihydro-1H-isoindol-2-yl)methyl]-1,2,3,4-tetrahydroisoquinolin-2-carbonyl]cyclohexane-1-carboxylic acid (compound (S,R,S)-1 a) was obtained. This X-ray crystal structure provides breakthrough experimental evidence for the true binding mode of the hit compound (S,R,S)-1 a, as the ligand orientation was found to differ from that of the initial docking model, which was available at the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 26 publications
(5 reference statements)
6
135
1
Order By: Relevance
“…The carboxamide group, which can form a similar hydrogen bond but has a significantly high pK a value, resulted in the inactive compound. This is consistent with the results provided by Jnoff et al 29 However, the carboxamide group can also be active in certain cases. The research of Jain et al 30 showed that when the substituent on the side-chain phenyl ring was the p-methoxy group, the diacetamide moiety can insert into the P1 and P2 subpockets and good inhibition activity can be retained.…”
Section: Potent Ppi Inhibition Activitysupporting
confidence: 93%
“…The carboxamide group, which can form a similar hydrogen bond but has a significantly high pK a value, resulted in the inactive compound. This is consistent with the results provided by Jnoff et al 29 However, the carboxamide group can also be active in certain cases. The research of Jain et al 30 showed that when the substituent on the side-chain phenyl ring was the p-methoxy group, the diacetamide moiety can insert into the P1 and P2 subpockets and good inhibition activity can be retained.…”
Section: Potent Ppi Inhibition Activitysupporting
confidence: 93%
“…Systems Medicine Approach to NRF2 in Chronic Diseases Five families of PPI inhibitors have been described: tetrahydroisoquinoline (Jnoff et al, 2014;Richardson et al, 2015), thiopyrimidine (Marcotte et al, 2013), naphthalene (Jiang et al, 2014b), carbazone (Ranjan et al, 2014), and urea derivatives (Sato et al, 2013). Table 3 compiles recent patents addressing these small molecules.…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…From the large number of compounds indexed in the available libraries, the compounds LH601, benzenesulfonylpyrimidone 2, N-phenyl-benzenesulfonamide, and a series of 1,4-diphenyl-1,2,3-triazoles might be very well-suited candidates to inhibit the PPI with KEAP1 (Hu et al, 2013;Jnoff et al, 2014;Bertrand et al, 2015;Wen et al, 2015;Nasiri et al, 2016). These studies described in detail the atomic interaction with KEAP1, the affinity, and the thermodynamics parameters of binding.…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…Limited variations to the structure resulted in compounds with a similar overall Keap1-binding affinity in the 1-2 μM range. The effect of these changes was rationalized using a series of crystal structures that demonstrated a binding orientation in which the tetrahydroisoquinoline occupies space in the channel that passes through the centre of the Kelch β-propeller structure [36].…”
Section: Tetrahydroisoquinolinesmentioning
confidence: 99%